EKSTENSI SIMBOLIK DOMINASI PRAKTIK KOMUNIKASI POLITIK (Reposisi Media dan Bingkai Kultural Masyarakat Terhegemoni Kekuasaan) - Abdul Halik (Fakultas Dakwah dan Komunikasi, 2017)
The objective classical approach dominates the theory and research of political communication. However, the increasingly dynamic practice of political communication encourages the emergence of other views which are more interpretive and subjective. In practice, political communication activities take place in cultural diverse contexts and therefore a variation of symbols in conveying political messages is required. The symbols of non-verbal communication are now used by political actors not only as a complement to verbal communication, but also as the message-code choices as important as the process of political communication.The media is exploited gently and ideologcally by political and economic power as a hegemonic power. Media put itself in the influence and dominance of a hegemonic power circle, so that the public space becomes narrower and less power.